(3efgGL GdYGQajf aj TQM cdGe CejQ GdeDefjf GdehShe HeGFI cdeIs - (3ejKe GdHMQGfj , ceGd GdOjf,J (B681 (3g` s
(3ChdgG (B:s
(3Gddge jG PG GdLdGd hGdEcQGe CeG HYO adeG cGf Gced GdSYGOGJ gh GdhUhd Edi GdhGMO GdMb hcGf ehdfG hCeGefG CejQ GdeDefjf Ydi Hf CHj WGdH s
(3BNQgG (B:s
(3Ke GYde Gfg dGjecfc GjgG GdedGMX HLdGd Gddg GdeJMQi Sdhc GdUQGW GdeSJbje hGLYd YhGbH GehQfG NjQkG s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B336 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B55s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI WgQGf (B(174) s
Keywords: (3GdJUha hGdBOGH GdTQYjIs